Usability Analysis of Trello Using the System Usability Scale (SUS) at the UIN Jakarta Career Development Center - Wijaya, Muhammad Willy; Waspodo, Bayu (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2024)
The UIN Jakarta Career Development Center is a dedicated unit focused on fostering the personal and professional growth of both current students and alumni of UIN Jakarta. Supported by student interns from diverse educational backgrounds and academic programs, the center operates daily to provide comprehensive services. These interns bring varied educational backgrounds and experiences, influencing their readiness to implement software for collaborative and coordinating purposes, replacing the previous system (Trello) at the UIN Jakarta Career Development Center. This study aims to evaluate Trello's effectiveness at the UIN Jakarta Career Development Center, intending to enhance the interns' performance and improve service delivery to uphold UIN Jakarta's reputation. The research methodology employs the System Usability Scale (SUS), with validity and reliability testing conducted using Cronbach's Alpha. Findings indicate that Trello's usability at the UIN Jakarta Career Development Center yields an average total score of 59.625 on the grade scale, categorizing usability as D with an adjective rating of OK and marginally acceptable. However, 37.5% respondents express skepticism regarding others' ability to quickly grasp Trello's use, while 55.5% state a need to acclimate themselves to Trello's usage. These insights underscore the importance of refining Trello's implementation to better support the center's operations and ensure a seamless user experience for interns and staff alike.